Implementasi Moderasi Beragama dalam Respon Agama Islam dan Kristen terhadap Modernitas - Malahayati, Putri; Harahap, Indra; Siregar, Husna Sari (Lembaga Yasin AlSys, 2024)
The research aims to explore the implementation of religious moderation in the response of Islamic and Christian religions to modernity. By highlighting the rapidly developing social, cultural and political context, this research pays attention to how these two main religions respond to the changes brought by modernity with a moderation approach. Through a descriptive qualitative approach involving literature analysis, this research examines how Islam and Christianity adapt to the challenges and opportunities posed by modernity. The main focus of research is on efforts to promote interfaith dialogue, tolerance, and deeper understanding between followers of different religions. The research findings show that, although the challenges of modernity may create tensions in religious interpretation and religious practice, there are promising trends in the implementation of religious moderation. In both Islamic and Christian contexts, efforts are seen to balance religious traditions with modern values such as democracy, human rights and pluralism. Meanwhile, challenges such as fundamentalism, radicalization and extremism remain obstacles in realizing comprehensive religious moderation. Nevertheless, this research highlights initiatives and practices that encourage interfaith dialogue, openness, and interfaith cooperation as positive steps in facing the complexities of modernity. This research contributes to further understanding of how major religions respond to the dynamics of modernity in a balanced and open way.